2014
DOI: 10.5194/bg-11-1775-2014
|View full text |Cite
|
Sign up to set email alerts
|

Foraminiferal species responses to in situ, experimentally induced anoxia in the Adriatic Sea

Abstract: Abstract. Anoxia was successfully induced in four benthic chambers installed at 24 m depth in the northern Adriatic Sea for periods varying from 9 days to 10 months. During the 10-month period, species richness significantly decreased. Although no significant change in Shannon diversity and evenness was observed, the composition of the foraminiferal assemblages changed with time. This change is due to interspecific differences in tolerance to anoxia. Reophax nanus, Textularia agglutinans and Quinqueloculina st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 95 publications
8
59
0
1
Order By: Relevance
“…In apparent contrast is an increase in the abundance of organic linings of benthic foraminifera. Some benthic foraminifera, however, tolerate low oxygen concentrations for substantial periods (Langlet et al, 2014) and may outcompete metazoans in such conditions (Woulds et al, 2007). This signal is surprisingly similar to that found in shelf sections of the Gulf of Mexico and Nigeria .…”
Section: Deoxygenation During the Petmsupporting
confidence: 68%
See 2 more Smart Citations
“…In apparent contrast is an increase in the abundance of organic linings of benthic foraminifera. Some benthic foraminifera, however, tolerate low oxygen concentrations for substantial periods (Langlet et al, 2014) and may outcompete metazoans in such conditions (Woulds et al, 2007). This signal is surprisingly similar to that found in shelf sections of the Gulf of Mexico and Nigeria .…”
Section: Deoxygenation During the Petmsupporting
confidence: 68%
“…Interestingly, the reduction in carbonate accumulation was most severe at Walvis Ridge and the Caribbean , both located towards the borders of the tropical band, which is in sharp contrast to sustained carbonate deposition in the Atlantic Southern Ocean sites 689 and 690 (Kelly et al, , 2010. Although carbonate wt % at Pacific tropical sites remains high (Colosimo et al, 2006;Leon-Rodriguez and Dickens, 2010), this is largely due to very low accumulation rates of the sole other sedimentary component, clay, and bioturbation, complicating robust estimates of carbonate accumulation through time.…”
Section: Potential Influence Of Heat Stress On Ocean Carbonate Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies within a given habitat typically concluded that of all permanent meiobenthic taxa, foraminiferans (see also Langlet et al, 2013) and nematodes are best adapted to hypoxia/anoxia and that crustaceans (e.g. copepods) are the least tolerant (see review by Wetzel et al, 2001).…”
Section: In Situ Experimentsmentioning
confidence: 99%
“…drug-multicellular parasites relation (TrejoChávez et al, 2011), phytoplankton ecology (Peperzak and Brussaard, 2011); and microbenthology -i.e. benthic microalgae, ciliates, flagellates and foraminiferans (Bernhard et al, 2003(Bernhard et al, , 2006Pucci et al, 2009;First and Hollibaugh, 2010;Figueira et al, 2012, Langlet et al, 2013a. The use of CTG for metazoan organisms, however, has so far been limited to dysoxic laminated sediments in 400 to 600 m water depth (oxygen minimum zone in the Santa Barbara Basin; Bernhard et al, 2003), and deep-sea (3300 to 3600 m) anoxic sediments (Mediterranean; Danovaro et al, 2010).…”
Section: Grego Et Al: Ctg Labelling Vs Rose Bengal Stainingmentioning
confidence: 99%